2002
DOI: 10.1038/ni758
|View full text |Cite
|
Sign up to set email alerts
|

Small anti-viral compounds activate immune cells via the TLR7 MyD88–dependent signaling pathway

Abstract: The imidazoquinoline compounds imiquimod and R-848 are low-molecular-weight immune response modifiers that can induce the synthesis of interferon-alpha and other cytokines in a variety of cell types. These compounds have potent anti-viral and anti-tumor properties; however, the mechanisms by which they exert their anti-viral activities remain unclear. Here we show that the imidazoquinolines activate immune cells via the Toll-like receptor 7 (TLR7)-MyD88-dependent signaling pathway. In response to the imidazoqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
1,634
4
36

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,215 publications
(1,709 citation statements)
references
References 46 publications
35
1,634
4
36
Order By: Relevance
“…Several studies using naturally mutant mice have implicated wild-type TLR4 in successful host defense against a variety of Gram-negative bacteria. The prototypic example is the C3H/HeJ mouse strain that is exquisitely sensitive to progressive, overwhelming infection by Salmonella typhimurium (LD 50 o2 colony forming units (CFU)) compared to closely related strains (LD 50 42 Â 10 3 CFU). 52 This strain was also shown to be hyporesponsive to the proinflammatory properties of purified LPS, and both phenotypes were mapped to a single genetic locus on chromosome 4 initially termed Lps.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using naturally mutant mice have implicated wild-type TLR4 in successful host defense against a variety of Gram-negative bacteria. The prototypic example is the C3H/HeJ mouse strain that is exquisitely sensitive to progressive, overwhelming infection by Salmonella typhimurium (LD 50 o2 colony forming units (CFU)) compared to closely related strains (LD 50 42 Â 10 3 CFU). 52 This strain was also shown to be hyporesponsive to the proinflammatory properties of purified LPS, and both phenotypes were mapped to a single genetic locus on chromosome 4 initially termed Lps.…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…Recent reports also suggest that mouse TLR7 and human TLR7 and TLR8 may participate in antiviral host defense, based on the observation that small antiviral imidazoquinoline compounds are capable of stimulating cellular activation through these receptors. 50,51 …”
Section: Viral Infectionmentioning
confidence: 99%
“…Both CpG-A and CpG-B have been shown to activate PDC via TLR9 [23]. Upon phagocytosis PDC lyse microorganisms in phagolysosomes, where microbial DNA interacts with and activates TLR9 derived from the endoplasmic reticulum [24].…”
Section: Introductionmentioning
confidence: 99%
“…1). Through this mechanism, TLR7 may receive [24][25][26][27] , several studies have indicated nonspecifi c effects of imiquimod on neurons. We have shown that imiquimod, CL075, and loxoribine restrict dendrite growth in wild-type rodent cortical and hippocampal neurons [11] .…”
Section: Endosomal Tlrs and Their Ligandsmentioning
confidence: 99%